IMPLIKATUR PERCAKAPAN DALAM STAND UP COMEDY INDONESIA DI STASIUN KOMPAS TV EDISI APRIL 2014 - Saputra Saputra; Mujiyono Wiryotinoyo; Akhyaruddin Akhyaruddin (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The problem in this research is what Lingual Forms Pragmatic Unit, and the Pragmatic Implications stand up comedyIndonesia Reuters TV station April 2014 edition of the method used in this research is descriptive qualitative method. Data collection techniques using techniques refer to. Data analysis is done in four steps, namely transcribe the data obtained, identify and classify the data, copy to the data card, and analyze the data card using pragmatic analysis. The results showed that 20 speech in Indonesia upcomedy stand in the April edition of Reuters TV station in 2014. The conclusion of the study forms lingual stand upcomedy conversational implicatures in the form of interrogative sentence, the sentence news, imperative sentences and exclamation sentences. Results of the research unit of pragmatic in a conversational implicatures upcomedyIndonesia stand at Reuters TV station April 2014 edition of the form, inform the facts, explain, reject, asserted, asked, ordered, and bans. Results of the research implications of pragmatic implicature percakapandalam stand upcomedyIndonesia Reuters TV station April 2014 edition of the form, reminiscent, complaining, comparing, amazed, invites, reject, scolding, insinuating, and inform the facts. Based on the research results, suggestions can be presented to users of the language in order to understand the implications pragmatic conversational implicatures in any event at the TV station, especially for lovers of stand-up comedy should be able to know the shapes sentences containing implicatures conversation so as to increase knowledge.